Zoom in on Butterflies - Melissa Stewart (USA Enslow Publishers, inc., 2023)
Another title in the Zoom In on Insects! series, ZOOM IN ON BUTTERFLIES takes an up close look at these beautiful insects. The 'Zoom Bubbles' offer a closer look at different butterfly body parts including the eyes, antennae, and wings. Lots of color photographs make it easy to understand exactly what the text is discussing.
Keywords: F & P - IR - L2 -- F & P - IR - L2